GIS-MULTI CRITERIA DECISION ANALYSIS FOR LAND ALLOCATION IN CONFLICTING PURPOSE Case Study: Adjoining Area of D’Aguilar National Park, Brisbane, Australia - Putra, Muhamad Iqbal Januadi (Badan Informasi Geospasial, 2021)
While there are much research has been conducted to apply the Multi-Criteria Decision Analysis (MCDA) and Geographic Information System (GIS) method to determine the suitability area for a particular purpose, only limited research has tried to examine the different approach to apply this method for the conflicting purpose. One area that has the potential to experience land use conflict in the future is the adjoining area of D’Aguilar National Park, Brisbane, Australia, due to the presence of biodiversity landscape value that needs to be protected. The objective of this paper is to allocate an area for each both residential development and conservation area in the adjoining area of D’Aguilar National Park. This research covers the method of GIS in processing the MCDA to develop the model which has many factors to support the decision making, including for the conflicting purpose. Moreover, the method also used GIS-fuzzy MCDA or widely known as GIS-Fuzzy MCDA (GIS-FMCDA). The result of this research shows that allocating the conflicting land area is quite different from the non-conflicting one. Applying MCDA for the conflicting purpose requires different decision making to show which area would be optimal to allocate.